The bully society : school shootings and the crisis of bullying in America's schools - Klein, Jessie (Intersections (New York, N.Y.), 2011)
In today's schools, kids abusing kids is not an occasional occurrence but rather an everyday reality where children learn early that being sensitive, respectful, and kind earns them no respect. Jessie Klein makes the provocative argument that the rise of school shootings across America, and childhood aggression more broadly, are the consequences of a society that actually promotes aggressive and competitive behaviour. The Bully Society is a call to reclaim America's schools from the vicious cycle of aggression that threatens our children and our society at large. Heartbreaking interviews illum.